2016
DOI: 10.1139/cjpp-2015-0578
|View full text |Cite
|
Sign up to set email alerts
|

Variation in stiffness regulates cardiac myocyte hypertrophy via signaling pathways

Abstract: Much diseased human myocardial tissue is fibrotic and stiff, which increases the work that the ventricular myocytes must perform to maintain cardiac output. The hypothesis tested is that the increased load due to greater stiffness of the substrata drives sarcomere assembly of cells, thus strengthening them. Neonatal rat ventricular myocytes (NRVM) were cultured on polyacrylamide or polydimethylsiloxane substrates with stiffness of 10 kPa, 100 kPa, or 400 kPa, or glass with stiffness of 61.9 GPa. Cell size incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
(49 reference statements)
0
18
0
Order By: Relevance
“…PKCɛ translocation has also been shown in vitro following CM stretch (Vincent et al, ). Our laboratory has demonstrated that mechanical stimulation through increased substrate stiffness or cyclic mechanical stretch leads to greater actin dynamics, which is mediated through a variety of signaling molecules, including PKCɛ, PIP2, and FAK (Li, Mkrtschjan, Lin, & Russell, ; Lin, Swanson, Li, Mkrtschjan, & Russell, ). It has been shown that isoproterenol treatment leads to rapid translocation of PKCɛ to the cell particulate fraction (Li, Cai, Liu, & Guo, ), making it a strong candidate here for implication in increased actin assembly rate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…PKCɛ translocation has also been shown in vitro following CM stretch (Vincent et al, ). Our laboratory has demonstrated that mechanical stimulation through increased substrate stiffness or cyclic mechanical stretch leads to greater actin dynamics, which is mediated through a variety of signaling molecules, including PKCɛ, PIP2, and FAK (Li, Mkrtschjan, Lin, & Russell, ; Lin, Swanson, Li, Mkrtschjan, & Russell, ). It has been shown that isoproterenol treatment leads to rapid translocation of PKCɛ to the cell particulate fraction (Li, Cai, Liu, & Guo, ), making it a strong candidate here for implication in increased actin assembly rate.…”
Section: Discussionmentioning
confidence: 99%
“…PKCɛ translocation has also been shown in vitro following CM stretch [Vincent et al, 2006]. Our lab has demonstrated that mechanical stimulation through increased substrate stiffness or cyclic mechanical stretch leads to greater actin dynamics, which is mediated through a variety of signaling molecules, including PKCɛ, PIP2, and FAK [J. Li et al, 2015; Lin et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations